Religious Values Approach And Family Support (Fs) Of Breastfeeding Campaign - Tri Hastuti Nur R, Tri Hastuti Nur R (2015)
Breastfeeding is proven to bring benefit for health, grow and development of babies. Despite of this, breastfeeding is not widely practiced in community and receives less support from government and health workers. This is due to several factors including myths and beliefs around breastfeeding; lack of information available on benefits of breastfeeding; very little support from family and workplace for an exclusive breastfeeding practices and assistance from health workers to mothers on importance of Early Initiation of Breastfeeding (IMD). Basic Health Research (2010) showed that exclusive breastfeeding behavior in Indonesia only reached 27.2%. This is much lower than government’ aim to reach 80% by 2014. Even the government has issued a Regulation Exclusive Breastfeeding number 33/2012. Aisyiyah as an Islamic women organization in Indonesia conducted campaigns in poor communities to increase breastfeeding practices. Poor communities lack of access on information of breastfeeding practices and immediate breastfeeding (IMD). Aisyiyah have been commitment to support breastfeeding practices and immediate breastfeeding for the better life of children on future. The campaigns were developed based on study to develop appropriate campaign messages and strategies. This paper presents finding of the evaluation of the Aisyiyah campaign. The methodology used was descriptive and the data collection was In depth Interview and Focus Group Discussion (FGD). Informants of In depth Interview are housewives that have babies, health cadre in communities and health worker. The participants of Focus Group Discussion (FGD) are housewives that have babies and their families. The evaluation found that the biggest challenge for breastfeeding practices was strong beliefs and myths uphold by women and their families. As well as of implementation Regulation Exclusive Breastfeeding number 33/2012. New strategies are needed to change behavior, there are inserting Islamic values in campaign messages on immediate breastfeeding practices, exclusive breastfeeding practices and health workers to provide assistance for women on immediate breastfeeding.